2020
DOI: 10.3390/app10041364
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Effect of Radiant Catalytic Ionization on the Bacterial Attachment and Biofilm Formation by Selected Foodborne Pathogens under Refrigeration Conditions

Abstract: The decontamination of food contact surfaces is a major problem for the food industry. The radiant catalytic ionization (RCI) method, based on the ionization process, may be an alternative for conventional decontamination procedures. The advantage of this technique is the possibility of its application to household refrigerating appliances and industrial cold rooms. This study aimed to assess the effect of RCI on the reduction of Campylobacter jejuni, Listeria monocytogenes, and Salmonella Enteritidis from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…RCI has been proven to act against biofilm formation. 15 It can operate safely in occupied spaces, preventing recontamination in real time. In 2020, a healthcare-specific air purifier based on RCI technology was registered and approved by the US Food and Drug Administration as a Class II Medical Device.…”
Section: Introductionmentioning
confidence: 99%
“…RCI has been proven to act against biofilm formation. 15 It can operate safely in occupied spaces, preventing recontamination in real time. In 2020, a healthcare-specific air purifier based on RCI technology was registered and approved by the US Food and Drug Administration as a Class II Medical Device.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown (Skowron et al 2018b) that the reduction of biofilm on biotic surfaces after the use of RCI for L. monocytogenes was from 3Á32% (salmon) to 41Á74% (carrot). In a study by Skowron et al (2020c), the highest E values for all species ranged from 0Á584 to 0Á725 and were obtained after 24 h of RCI application to the surface contaminated for 12 h (experimental variant I). On the contrary, a significant reduction was not observed on the glass surface covered with the contaminated meat sample during 72 h exposure of RCI (variant III).…”
Section: Radiant Catalytic Ionization-antimicrobial Effectmentioning
confidence: 97%
“…This technology is effective in low temperatures as presented for bacterial biofilm in the case of L. monocytogenes (biotic and abiotic surfaces) (Skowron et al 2018b) and Campylobacter jejuni, L. monocytogenes and Salmonella Enteritidis on the glass surface under refrigerated conditions (Skowron et al 2020c) (Table 3). The reduction rate in the number of L. monocytogenes in biofilms formed on various surfaces (rubber, milled rock tiles, polypropylene) ranged from 3Á92% to 70Á10%, while in the case of AISI 304 stainless steel and lacquered veneer surfaces, up to 95% of L. monocytogene were reduced (Table 3).…”
Section: Radiant Catalytic Ionization-antimicrobial Effectmentioning
confidence: 99%
“…Moreover, the plasma species were able to penetrate the deeper layers of the model biofilms and some treatment conditions resulted in an increased biofilm porosity. Skowron et al [2] reported the efficiency of the Radiant Catalytic Ionization (RCI) method in the reduction of bacteria number from a glass surface. Bonneville et al [3] suggested that biofilm behavior depends on the strain and sub-inhibitory concentrations of disinfectants and may explain the ability of certain isolates to persist in niches of food processing plants.…”
mentioning
confidence: 99%